1986
DOI: 10.1002/path.1711480203
|View full text |Cite
|
Sign up to set email alerts
|

Expression of low molecular weight cytokeratin proteins in cervical neoplasia

Abstract: CAM 5.2 is a monoclonal antibody which identifies lower molecular weight cytokeratin proteins (50, 43 and 38 kD). It is an antibody which works reliably on formalin-fixed, paraffin-embedded tissues. In this study, using CAM 5.2 in the indirect immunoperoxidase method we have examined ectocervical epithelium ranging from normal, through metaplasia and cervical intraepithelial neoplasia to invasive squamous carcinoma. CAM 5.2 is demonstrated to be a useful indicator of changes associated with malignant transform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
16
1

Year Published

1988
1988
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 9 publications
4
16
1
Order By: Relevance
“…While normal cervical stratified squamous epithelium expresses high molecular weight cytokeratins, all non-keratinising invasive squamous carcinomas and some cases of CIN3 express low-molecular weight cytokeratins as well as those of high molecular weight (Whittaker et al, 1989;Raju, 1988;Bobrow et al, 1986). Using monoclonal antibody NCL-5D3, recognising cytokeratins 8, 18 and 19 (Angus et al, 1987) we have confirmed these observations (Angus et al, 1988 (Sterrett et al, 1987).…”
supporting
confidence: 74%
“…While normal cervical stratified squamous epithelium expresses high molecular weight cytokeratins, all non-keratinising invasive squamous carcinomas and some cases of CIN3 express low-molecular weight cytokeratins as well as those of high molecular weight (Whittaker et al, 1989;Raju, 1988;Bobrow et al, 1986). Using monoclonal antibody NCL-5D3, recognising cytokeratins 8, 18 and 19 (Angus et al, 1987) we have confirmed these observations (Angus et al, 1988 (Sterrett et al, 1987).…”
supporting
confidence: 74%
“…In this study, the expression of keratin 8 (CAM 5.2) was increased up to about 77% of CIN III, compared to 15% of CIN I and II. The positive percentage of keratin 8 expression found in up to 77% of CIN III was considerably higher than that found by Bobrow et al [3] and Angus et al [1], possibly because of the effect of formalin fixation and paraffin embedding. Smedts et al [13,15] showed that CAM 5.2 (keratin 8) reacted with 50% of CIN III, which were frozen materials.…”
Section: Cervical Intraepithelial Neoplasiacontrasting
confidence: 58%
“…Goellner (1976) Immunohistochemistry has as yet been of limited value as a tool for predicting behaviour of cervical dysplasia and neoplasia. Bobrow et al (1986) have suggested that a change in cytokeratin expression by neoplastic cervical epithelium (CIN) as reflected by different degrees of staining with the anti-cytokeratin antibody CAM 5.2, may be a marker of invasive potential. This conclusion has not however been confirmed by a similar study conducted by Wells et al (1986).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical behaviour of invasive carcinoma of the cervix is not uniform but covers a wide spectrum from cases that are relatively indolent to those having a rapidly progressive course (Richart & Barton, 1969 (Ng & Atkin, 1973;van Nagell et al, 1977;Bobrow et al, 1986) and opponents (Crissman et al, 1985;Goellner, 1976;Wells et al, 1986;Fray et al, 1984).…”
mentioning
confidence: 99%